2012
DOI: 10.1100/2012/837395
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Growth Regulators on Callogenesis and Somatic Embryo Development in Date Palm (Phoenix dactyliferaL.) Sahelian Cultivars

Abstract: This study provides a physiological analysis of somatic embryogenesis in four elite cultivars of date palms: Ahmar, Amsekhsi, Tijib, and Amaside, from the initial callogenesis to establishment and proliferation of embryogenic suspension cultures. Somatic embryos development and in vitro plants rooting were also studied. For each step, auxins and cytokinins concentrations were optimised. The primary callogenesis from leaf explants of seedlings appeared highly dependent on genotype. Ahmar (80%) and Amsek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
1
15
0
2
Order By: Relevance
“…High callogenesis rates were also obtained in the presence of the combinations of 2,4-D with BA in date palm (Ahmar and Amsekhsi cultivar), which corresponded with our results. It has also been observed that the application of high concentrations of cytokinin caused a reduction of callogenesis (Sane et al, 2012). Vescovi and coworkers (2012) also found that the use of high levels of BA (9 mg/l) induced the apoptosis of the cells in the cultures of Arabidopsis thaliana.…”
Section: Plant Growth Regulators' Effect On Callogenesis and Direct Ementioning
confidence: 95%
“…High callogenesis rates were also obtained in the presence of the combinations of 2,4-D with BA in date palm (Ahmar and Amsekhsi cultivar), which corresponded with our results. It has also been observed that the application of high concentrations of cytokinin caused a reduction of callogenesis (Sane et al, 2012). Vescovi and coworkers (2012) also found that the use of high levels of BA (9 mg/l) induced the apoptosis of the cells in the cultures of Arabidopsis thaliana.…”
Section: Plant Growth Regulators' Effect On Callogenesis and Direct Ementioning
confidence: 95%
“…Plant growth regulators (PGRs) are the substances that influence physiological processes of plants at very low concentrations and modify or control one or more specific metabolic events of a plant (Danova et al 2012;Sane et al 2012). According to the Environmental Protection Agency (EPA), the plant regulators have been defined as "any substance or mixture of substances intended, through physiological action, to accelerate or retard the rate of growth or maturation, or otherwise alter the behaviour of plants or their produce".…”
Section: Some Examples Of Positive Plant Growth Regulators Synthesizementioning
confidence: 99%
“…In the absence of auxins, 58% of rooting occurred after 150 d of cultivation. In E. guineensis and Phoenix dactylifera, shoots derived from embryo multiplication also showed development of roots in auxin-free media, although auxin supplementation favored rooting (Nizam and Te-Chato 2009;Sumaryono and Riyadi;2011;Sané et al 2012). These results likely can be explained by the existence of natural auxins, such as indole-3-acetic acid (IAA), in the tissues of the explants, or by the residual effects of the auxins used in the induction and multiplication phases of the embryogenic cultures (Klerk et al 1999).…”
Section: Resultsmentioning
confidence: 99%